Development of classification module for automated question generation framework - Gyöngyösi, Erika; Kovács, László; Bednarik, László (Teaching Mathematics and Computer Science, 2013)
Automatic question generation is in the focus of recent researches which includes bordering disciplines like education, text mining, knowledge-engineering. The elaborated system generates multi-choice questions from textbooks without using an external semantic database. One of the base modules of the system is the classification module defining the extracted word. This paper describes modules of the framework including a detailed analysis of the classification part. We show the operability of the elaborated system through a practical test.